Language and linguistics in a complex world - Busse, Beatrix; Dumrukcic, Nina; Kleiber, Ingo (Diskursmuster, 2023)
This book is a collection of the ICAME41 conference proceedings covering a range of topics in corpus linguistics. Busse et al. Explore contemporary trends and new directions in the field. Papers focusing on historical linguistics include Bohmann et al's study on the passive alternation in 19th and 20th century American English whilst Iyeiri and Fukunaga investigate negation in 19th century American missionary documents. Bohmann's emphasis is on the Contrastive usage profiling method to represent online discourse data. Empirical studies on discourse analysis include Brooks' analysis of how the UK press portrays obesity, Coats generating ASR transcripts to look at dialect data from YouTube, and Gonzalez-Cruz's pragmatic considerations of Anglicisms entering Canarian-Spanish digital headlines. Schneider use statistical models to look at language comprehension in an eye-tracking corpus